Elevated Levels of Adhesion Proteins Are Associated with Low Ankle-Brachial Index: Multi-Ethnic Study of Atherosclerosis - Berardi, Cecilia (Angiology, 2016)
Inflammation plays a pivotal role in peripheral artery disease (PAD). Cellular adhesion proteins mediate the interaction of leukocytes with endothelial cells during inflammation. To determine the association of cellular adhesion molecules with ankle-brachial index (ABI) and ABI category (≤1.0 vs. >1.0) in a diverse population, fifteen adhesion proteins were measured in the Multi-Ethnic Study of Atherosclerosis (MESA). To assess multivariable associations of each protein with ABI and ABI category, linear and logistic regression was used, respectively. Among 2364 participants, 23 presented with poorly compressible arteries (ABI>1.4) and were excluded and 261 had ABI ≤1.0. Adjusting for traditional risk factors, elevated levels of soluble P-selectin, Hepatocyte Growth Factor and Secretory Leukocyte Protease Inhibitor were associated with lower ABI (P = .0004, .001 and .002, respectively). Per each standard deviation of protein, we found 26%, 20%, and 19% greater odds of lower ABI category (P = .001, .01 and .02, respectively).. Further investigation into the adhesion pathway may shed new light on biological mechanisms implicated in PAD.